2016
DOI: 10.1002/jsfa.7617
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-based technology ameliorates glandular trichomes, secondary metabolites and antioxidants inPelargonium graveolensL'Hér.

Abstract: The present study highlights an explicit amalgamation of prospective microbes showing potential for synergism that act as biostimulants in enhancing plant production and improving the antioxidant and aroma profile of P. graveolens. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Alike, P being a component of EO precursors (isopentyl diphosphate and dimethylallyl diphosphate) can also enhance EO production (Dehsheikh et al, 2020). The observed increase in EO yield reported in the current investigation might be attributed to the increased number of glandular trichomes and antioxidants, as some posterior studies have already claimed these factors are responsible for the increase in EO yield after combined treatment of plant beneficial microbes in MAPs like sweet basil (Gupta and Pandey, 2015) and Pelargonium graveolens L'Heŕ (Gupta et al, 2016).…”
Section: Essential Oil Content Yield and Compositionsupporting
confidence: 55%
“…Alike, P being a component of EO precursors (isopentyl diphosphate and dimethylallyl diphosphate) can also enhance EO production (Dehsheikh et al, 2020). The observed increase in EO yield reported in the current investigation might be attributed to the increased number of glandular trichomes and antioxidants, as some posterior studies have already claimed these factors are responsible for the increase in EO yield after combined treatment of plant beneficial microbes in MAPs like sweet basil (Gupta and Pandey, 2015) and Pelargonium graveolens L'Heŕ (Gupta et al, 2016).…”
Section: Essential Oil Content Yield and Compositionsupporting
confidence: 55%
“…Endophytes are known to exert beneficial effect on plants by assisting in an adjustment of plant phenolic compound content and anti-oxidative systems in response to unfavorable conditions [15,16]. Anti-radical activity of certain medicinal plants is promoted by endophytic microorganisms [17]. Antibiotic treated S. nigra flowers were likely deprived of TPC-and ARA-promoting effect of endophytes leading to a significantly decreased TPC and ARA.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum increase in withaferin A by 4.00 fold was recorded in BS_CC followed by 3.00 fold in both STR_CF and TH_CC treatments as compared to the control plants (Table 1). Recently, a study showed that application of plant growth promoting microbes significantly enhanced secondary metabolite content in medicinal and aromatic plants like Bacopa monnieri, W. somnifera and Pelargonium graveolens (Rajasekar and Elango 2011;Gupta et al 2015bGupta et al , 2016. Increase in antioxidant capacity in TH_CF could also be positively correlated with increased Withanolide A, a well known antioxidant molecule.…”
Section: Resultsmentioning
confidence: 99%